Continuous deformation analysis and contact force estimation for pneumatic bending actuators interacting with environment - Namdar Ghalati, Mohammad Hadi; Ghafarirad, Hamed (Comptes Rendus. Mécanique)
Soft bending actuators show high adaptability for applications such as rehabilitation or grasping. Although constant curvature assumption has been extensively used for free motion modeling, these actuators do not bend circularly when interacting with the environment. In such situation, conventional bending sensors cannot provide useful information on their shape. In this paper, the Finite Rigid Elements approach is utilized to model the behavior of a soft pneumatic bending actuator in free motion and contact. With this method, the variable curvature configuration under different external loads can be modeled. Then, the contact force between the actuator and an object located in a specific position is estimated utilizing the Gradient Descent optimization method. Experimental results verified the combinatorial proposed approach for both force estimation and structure deformation.